1982
DOI: 10.1002/jso.2930190202
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral cavity in young adults

Abstract: The 12 patients less than 35 years of age treated for squamous cell carcinoma of the oral cavity at the American Oncologic Hospital between 1954-1979 are examined. Group A (eight patients) had involvement of the tongue; Group B (4 patients) had carcinoma of other oral sites. Mean "T" stage for Group A and Group B was 1 and 1.5, respectively. Treatment was surgical in the majority of cases. Seventy-one percent of Group A and 25% of Group B developed metastatic disease to the neck. The 2-year survival rate was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
1
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 5 publications
3
53
1
1
Order By: Relevance
“…This is similar to the rate of tobacco use in young patients with head and neck cancer reported in other series. [1][2][3]8,[10][11][12] The older group had a slightly higher smoking prevalence: 58%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the rate of tobacco use in young patients with head and neck cancer reported in other series. [1][2][3]8,[10][11][12] The older group had a slightly higher smoking prevalence: 58%.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors conclude that these patients have a worse outcome than their older counterparts. [1][2][3][4] Son and Kapp 1 reviewed the Yale-New Haven Medical Center experience from 1958 through 1980. They identified 27 patients below the age of 40 years with SCC of the oral cavity and oropharynx.…”
mentioning
confidence: 99%
“…Studies on whether the age at diagnosis affects the prognosis revealed conflicting data. 5 Son and Kapp, 2 Amsterdam and Strawitz, 6 and Sarkaria and Harari 7 concluded that young patients have worse outcomes than their older counterparts. 5 There is a generally held view that oral cancers in young people are more aggressive and have a worse prognosis.…”
Section: Introductionmentioning
confidence: 98%
“…While the definition of what age constitutes a young head and neck patient is arbitrary, most series have assigned this definition to patients aged less than 40 years [1][2][3] although authors have used 30, 4 35, 5 and 45 6 years as an upper limit for this group.…”
Section: Introductionmentioning
confidence: 99%